On the determination of the signs of sources of financial law - Дмитрик, О. О. (Theory and practice of jurisprudence, 2016)
The author focuses on the consideration of sources of financial law. Based on the analysis of a monographic literature highlighted the inherent characteristics of such sources, including: formal certainty, normative, universal validity, validity, common knowledge, consistency, the publication by the authority.